2018
DOI: 10.1038/s41467-018-04774-9
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 accelerates retinal development via the immunoproteasome

Abstract: The numbers and types of cells constituting vertebrate neural tissues are determined by cellular mechanisms that couple neurogenesis to the proliferation of neural progenitor cells. Here we identified a role of mammalian target of rapamycin complex 1 (mTORC1) in the development of neural tissue, showing that it accelerates progenitor cell cycle progression and neurogenesis in mTORC1-hyperactive tuberous sclerosis complex 1 (Tsc1)-deficient mouse retina. We also show that concomitant loss of immunoproteasome su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 64 publications
7
34
1
Order By: Relevance
“…Subsequently, similar approaches to perturb the pathway demonstrated its involvement elsewhere in the CNS, including in the regeneration of axons in the corticospinal tracts (Du et al, 2015;Liu et al, 2010;Zukor et al, 2013). We demonstrate that, much like in rodents, the mTOR pathway plays an important role in the development of hRGCs (Choi et al, 2019) and regeneration of their axons (Park et al, 2008), and is therefore an important molecular target for establishing a disease model of glaucomatous degeneration and therapeutic RGC regeneration. This premise is supported by the following observations.…”
Section: Discussionmentioning
confidence: 70%
“…Subsequently, similar approaches to perturb the pathway demonstrated its involvement elsewhere in the CNS, including in the regeneration of axons in the corticospinal tracts (Du et al, 2015;Liu et al, 2010;Zukor et al, 2013). We demonstrate that, much like in rodents, the mTOR pathway plays an important role in the development of hRGCs (Choi et al, 2019) and regeneration of their axons (Park et al, 2008), and is therefore an important molecular target for establishing a disease model of glaucomatous degeneration and therapeutic RGC regeneration. This premise is supported by the following observations.…”
Section: Discussionmentioning
confidence: 70%
“…MTORC1 signaling was also enriched and is known to crosstalk with the Hippo pathway ( Tumaneng et al, 2012 ). The phosphatidylinositol 3-kinase (PI3K)-Akt-mTORC1 pathway has been discovered to promote mouse RPC proliferation by regulating the synthesis and degradation of CYCLIN proteins with the interesting exception of CYCLIN D1 ( Choi et al, 2018 ). MTOR was also shown to be required for chick MG proliferation in response to damage ( Zelinka et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that mTOR regulated the proliferation and differentiation of retinal progenitor cells in the ciliary marginal zone in Xenopus (Love, Keshavan, Lewis, Harris, & Agathocleous, 2014). A recent study also reported that mTORC1 accelerated the cell cycle progression and neurogenesis of retinal progenitors via the immunoproteasome during mouse development (Choi et al, 2018).…”
Section: Introductionmentioning
confidence: 97%